Предмет: Математика,
автор: deathmod
Преобразуйте в многочлен: (2а+4)(2а-4)
Помоги быстрее
Ответы
Автор ответа:
0
По формуле (a-b)(a+b)=a^2-b^2 мы получаем:
=4a^2-16
Преобразование таково.
=4a^2-16
Преобразование таково.
Автор ответа:
0
|объяснение к решению:а^2=а*а, *-умножить
|решение:
так как (a-b)*(a+b)=a^2-b^2
то зн (2а-4)*(2а+4)=(2а)^2-(4)^2=
2*2*а*а-4*4=
4а^2-16
|Ответ:4а^2-16
|решение:
так как (a-b)*(a+b)=a^2-b^2
то зн (2а-4)*(2а+4)=(2а)^2-(4)^2=
2*2*а*а-4*4=
4а^2-16
|Ответ:4а^2-16
Похожие вопросы
Предмет: Математика,
автор: Ychenuk222228888
Предмет: Физика,
автор: fawertyhgdy
Предмет: Биология,
автор: n1kitosikkk
Предмет: Математика,
автор: ozerovaalena